Researching religious authority in education: Political theology, elites’ theory and the double nexus - Gearon, L; Kuusisto, A (SAGE Publications, 2018)
This article provides a theoretical frame to structure methodological approaches to examining religious authority in education. It does so by examining the complex, overlapping relationship between secular and religious authority and the institutional power of education evident through responses to issues of cultural expression. The political theologies research examined ongoing tensions – accommodations, conflicts and resolutions – of religious authority with secular political systems, legal frameworks and institutions of educational replication. Through the data it became clear that education – in the broadest sense, as well as in its formal institutional structures – provided a mediating role for power exchanges between religious and political authority, which was especially evident in responses of religious leaders to issues of cultural and self-expression. Through interviews with senior religious leaders and authority figures in England – technically religious ‘elites’ – the findings provide insights into a ‘double nexus’ conceptual framework for researching religious authority in education: first, the internal nexus within religious traditions and, second, the external nexus of religious communities with secular, legal and political authority. Theoretically and methodologically, this represents a critical synthesis of political theology and elites’ theory, providing as yet underexplored possibilities for researching religious authority in education.